Tumor Immunometabolism Characterization in Ovarian Cancer With Prognostic and Therapeutic Implications - Yang, Miner; Chen, Gaowen; Gao, Kunjie; Wang, Yifeng (Frontiers in Oncology, 2021)
Metabolic dysregulation in the tumor microenvironment has significant impact on immune infiltration and immune responses. However, interaction between immunity and metabolism in the ovarian microenvironment requires further exploration. We constructed an immunometabolism gene set and ovarian cancer cohort from The Cancer Genome Atlas (TCGA) and classified these into three immunometabolism subtypes. We explored the relationships between immune infiltration and metabolic reprogramming. Additionally, we built risk score and nomogram as prognostic signatures. Three distinctive immunometabolism subtypes were identified with therapeutic and prognostic implications. Subtype 1, the “immune suppressive-glycan metabolism subtype,” featured high levels of immunosuppressive cell infiltration and glycan metabolism activation; Subtype 2, the “immune inflamed-amino acid metabolism subtype,” showed abundant adaptive immune cell infiltration and amino acid metabolism activation; Subtype 3, the “immune desert-endocrine subtype,” was characterized by low immune cell infiltration and upregulation of hormone biosynthesis. Furthermore, we found that epinephrine biosynthesis displayed a significantly negative correlation with MHC molecules, which may result in defective antigen presentation. We proposed immunometabolism subtypes with prognostic implications and provided new perspectives for the ovarian cancer microenvironment.